Estimates of the Kolmogorov Widths of Classes of Analytic Functions Representable by Cauchy-Type Integrals. I - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
In the Banach space of functions analytic in a Jordan domain \(Ω C\) , we establish order estimates for the Kolmogorov widths of certain classes of functions that can be represented in Ω by Cauchy-type integrals along the rectifiable curve Γ = ∂Ω and can be analytically continued to Ω′ ⊃ Ω or to \(C\) .